2015
DOI: 10.2174/092986652210150821170703
|View full text |Cite
|
Sign up to set email alerts
|

Design of Phenylalanine-Containing Elastin-Derived Peptides Exhibiting Highly Potent Self-Assembling Capability

Abstract: In this study, we developed a series of Phe-containing elastin-derived peptide-analogs, (Phe-Pro-Gly-Val-Gly)n (n = 1-5) and analyzed their reversible coacervation properties. Compared to the native elastin-derived repeating peptide sequence ((Val-Pro-Gly-Val-Gly)10), one of the Phecontaining 5-mer repeating peptide sequences ((Phe-Pro-Gly-Val-Gly)5) clearly exhibited stronger coacervation properties. The coacervation of (Phe-Pro-Gly-Val-Gly)5 is nearly the same as that of polypeptides (Val-Pro-Gly-Val-Gly)n (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 0 publications
6
32
0
Order By: Relevance
“…The N-dimer spectrum showed a prominent negative band at 197 nm, a positive band at 220 nm and a minor negative band at 236 nm (Figure 4). These features are similar to the CD spectra of the (FPGVG) 5 monomer [11]. Furthermore, the CD measurements showed that the dimers exhibited reversible temperature-dependent spectral changes, although the degree of alteration was lower than that observed for the (FPGVG) 5 monomer [11].…”
Section: Measurementsupporting
confidence: 71%
See 2 more Smart Citations
“…The N-dimer spectrum showed a prominent negative band at 197 nm, a positive band at 220 nm and a minor negative band at 236 nm (Figure 4). These features are similar to the CD spectra of the (FPGVG) 5 monomer [11]. Furthermore, the CD measurements showed that the dimers exhibited reversible temperature-dependent spectral changes, although the degree of alteration was lower than that observed for the (FPGVG) 5 monomer [11].…”
Section: Measurementsupporting
confidence: 71%
“…In contrast, the (FPGVG) 5 monomer did not show any increase in turbidity under the same conditions (Figure 3a). Previous studies reported that this monomer requires a higher temperature (T t = 38.0°C) and at least 3× higher concentration (30 mg/ml) to consistently achieve coacervation (Figure 3b) [11]; coacervation was not always apparent at a concentration of 20 mg/ml. These results suggest that the dimerization of elastin-derived peptide analogs enhanced the coacervation ability of (FPGVG) 5 .…”
Section: Coacervation Of Elastin-derived Peptidesmentioning
confidence: 77%
See 1 more Smart Citation
“…Previously, we performed reversed-phase HPLC analyses for various elastin-derived peptides using an ODS (octadecylsilyl) column. From these results, a correlation between the coacervation property and the retention time was observed [17,18]. Therefore, we performed reversed-phase HPLC analyses for all peptides used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…We have reported that an elastin-derived peptide analog, in which Val at position 1 in the representative elastin-derived sequence VPGVG was substituted by the more hydrophobic amino acid Ile [17], exhibited enhanced coacervation. Furthermore, the substitution by the aromatic amino acid Phe at position 1 revealed a more potent coacervation property than exhibited by the Ile-containing elastin-derived peptides [18]. Although the hydrophobicity of Phe is generally considered less than that of Ile [25], the Phe substitution led to a more enhanced coacervation potency than did the Ile substitution.…”
Section: Discussionmentioning
confidence: 99%